Antibodies against toxoplasma gondii in horses with history of ataxia - Stelmann, Ulisses Jorge Pereira; Da Silva, Rodrigo Costa [UNESP]; Langoni, Hélio [UNESP]; Borges, Alexandre Secorum [UNESP]; Amorim, Rogério Martins [UNESP] (My University, 2011)
The frequency of antibodies in blood serum and cerebrospinal fluid against Toxoplasma gondii in horses with a history of ataxia from the state of Sao Paulo, Brazil was carried out. Modified agglutination test was used to determine antibodies against T. gondii, considering as positive samples with titers ≥ 2. Of the blood samples tested, only 8 of 23 (34.78%) were positive, while CSF samples were negative when used the same technique. According to the negative results obtained for CSF, we concluded that T. gondii was not the etiological agent of the myeloencephalitis in studied horses with neurological manifestation of ataxia, while the blood serological results indicated a previously exposure to T. gondii.
Anticorpos contra toxoplasma gondii em equinos com histórico de ataxia
Keywords: Ataxia; Cerebrospinal fluid; Horses; Toxoplasma gondii; Toxoplasmosis